A relay path selection method for video streaming on shared terminals. (1st January 2011) - Kawano, Yasuhiro; Hashimoto, Koji; Shibata, Yoshitaka
As broadband network services and video streaming systems become more common, high-definition (HD) quality stream format has become increasingly popular in live video distribution. Today's video streaming systems are used for a variety of purposes, but those systems require much bandwidth and CPU power for video streams. In this paper, we focus on the design of a relay path selection method on community-based resource sharing networks, which is able to select and use suitable stream paths cooperatively in sharing resources. On live video distribution, a candidate relay path list is created when users request to receive live video streams, and the best path is selected. If a new relay node is required, the suitable relay node is placed on a shared terminal in consideration of available resource status. Our experiments by a prototype system show that our method is successful in realisation of the suitable relay path selection and live video streaming on shared terminals.